Profile of biogenic amines and their correlations with chemical constituents and some properties of Egyptian Ras cheese - Swelam, Seham S (Indian Journal of Dairy Science, 2017)
A total of ten market Ras cheese samples were randomly collected and analysed for biogenic amines (BAs) content, gross chemical composition and some ripening indices.The attained results revealed that the average of the total measured BAs was 344.7± 30.43 which included the following BAs in mg/100g: histamine (Him), tyramine (Tym), tryptamine (try), putrescine (Put), cadaverine (Cad), β-phenylethylamine (Phe), spermidine (Spd) and spermine (Spm). The recorded average values for the detected BAs were114.90, 1.22, 14.97, 119.50, 77.73, 22.58, traces and traces respectively. Marked variations were observed in the gross chemical composition of the samples which characterized also by varied acidity and pH values as well as the ripening indices SN/TN and formol ripening index (FRI). Statistical analysis showed that a highly significant negative correlation was recorded between TBAs and moisture content, whereas the correlation between TBAs and salt/ moisture was positive (P≤0.01). Him content was negatively correlated with FRI (P≤0.05) and positively correlated with SN/TN (P≤0.05). Highly significant negative correlations were recorded between Tym, Try and Put with moisture, whereas their correlations with salt/ moisture were positive (P≤0.01). Cad was positively correlated with salt, salt/moisture and FRI and negatively correlated (P≤0.01) with pH. Phe showed positive correlations with the salt/moisture, pH and the ripening indices.